Economic and Geographic Problems of Improvement of Industrial Sectors and Local Structure of Uzbekistan - KOMILOVA, Nilufar Kh.; HUDAYBERGANOVA, Rukhsora T.; MURTAZAEV, Isabek B.; ABDINAZAROVA, Hidoyathon O.; MADAMINOV, Zafarjon H. (Journal of Advanced Research in Law and Economics, 2019)
Industry is the leading production sector of the national economy and forms the financial basis of society. Acceleration of economic development of the country, improvement of production efficiency depends on the development of the industrial sector. Modernization and diversification of production, technical and technological renovation, high-tech processing tar justified on the basis of deep processing of local raw material resources and the development of cooperation ko'zlangangan. At the same time, the main objectives of the efficient and optimal use of the regional potential, including reducing the disparities in the socio-economic development of the regions through modernization and diversification of the economy of the regions, are to increase industrial and export potential, to establish industrial poles. The role of industry in the regional sustainable socio-economic development of the country, on the contrary, has a negative impact on the development of the regions and the country. Therefore, a special role in the development of industrial sectors and improvement of the territorial structure of regions of the republic is to study the impact of existing natural and environmental and socio-economic factors, periodic and regional aspects of production diversification.